Effectiveness of Yoga Training Combined with Healthy Lifestyle Education on Body Image Attitudes and Postural Improvement in Individuals with Postural Abnormalities and Sedentary Behaviors - Saleh, Afagh; Agahheris, Mojgan; Kordmirza Nikoozadeh, Ezzatolah; Rafiepoor, Amin; Karami Baghteyfouni, Zahra (Journal of Assessment and Research in Applied Counseling (JARAC), 2026)
Objective: This study aimed to determine the effectiveness of a combined yoga and healthy lifestyle education program in improving body image attitudes and postural status among individuals with postural abnormalities and sedentary behaviors.Methods and Materials: This quasi-experimental study employed a pretest–posttest control-group design with a two-month follow-up. The statistical population consisted of women and men with postural abnormalities and sedentary behaviors who attended healthcare centers in Tehran, Iran. Using purposive sampling, 40 eligible participants with a mean age of 47.05 years were selected and randomly assigned to an experimental group (n = 20) or a control group (n = 20). The experimental group received ten weekly 60-minute yoga sessions and ten weekly 60-minute healthy lifestyle education sessions, whereas the control group received no intervention during the study period. Data were collected using the Multidimensional Body-Self Relations Questionnaire developed by Winstead and Cash (1984) and digital photogrammetric postural assessment conducted using APECS software. The data were analyzed using mixed multivariate analysis of variance with repeated measures and Bonferroni post hoc comparisons.Findings: The results demonstrated significant effects of time and the group-by-time interaction on body image attitudes (Wilks’ lambda = 0.049, F = 357.507, p < 0.001, η² = 0.951) and postural status (Wilks’ lambda = 0.001, F = 5659.228, p < 0.001, η² = 0.999). Bonferroni pairwise comparisons indicated significant improvements from pretest to posttest and from pretest to follow-up in the experimental group compared with the control group. No significant differences were observed between posttest and follow-up scores for either outcome, indicating that the intervention effects were maintained over the two-month follow-up period.Conclusion: Yoga training combined with healthy lifestyle education appears to be an effective and sustainable intervention for improving body image attitudes and postural status in individuals with postural abnormalities and sedentary behaviors. Integrating physical, behavioral, and lifestyle-oriented components may provide a comprehensive approach to reducing the physical and psychological consequences associated with inactivity and poor posture.